Analisis Framing Media: Debat Menteri Keuangan dan Komisi XI tentang Tenaga Kerja Migran Indonesia - Karmanto Karmanto; Kelly Ayu Anggraeni; Nani Nurani Muksin; Rahmat Salam (SENTRI: Jurnal Riset Ilmiah, 2025)
The debate between the Indonesian Minister of Finance and Commission XI of the House of Representatives (DPR RI) regarding the issue of Indonesian citizens who are compelled to work abroad has drawn significant public attention and generated dynamic coverage across various national media outlets. This study aims to analyze how the media frame this polemic by employing Robert Entman’s framing model, which consists of four elements: problem definition, causal interpretation, moral evaluation, and treatment recommendation. The research adopts a qualitative approach with a media discourse analysis design. Data were collected through documentation of news articles published by several national online media during the period in which the polemic unfolded. Samples were selected purposively based on the relevance of the news content and were subsequently analyzed using Entman’s framing indicators. To maintain data credibility, source triangulation and intercoder consistency checks were conducted. The findings reveal a contestation of framing among media outlets: some emphasize domestic structural issues such as economic inequality and limited job opportunities, while others reinforce the government’s narrative regarding global economic prospects and efforts to enhance the competitiveness of Indonesian workers. These findings highlight the role of media as a site of meaning contestation that shapes public perceptions of labor migration issues. The study underscores the importance of understanding framing dynamics to critically interpret media narratives, particularly those related to employment and migration.